PENINGKATAN KEMAMPUAN MENULIS TEKS BERITA MELALUI STRATEGI THINK TALK WRITE DENGAN MENGGUNAKAN FOTO PERISTIWA - ZAIDAR - - (Jurnal Tunas Pendidikan, 2020)
This study examines the improvement of the ability to write news texts through the Think Talk Write (TTW) strategy by using photos of events on class XI OTKP students of SMK Negeri 1 Muara Bungo. The purpose of this study was to describe the increase in the ability of Class XI OTKP students of SMK Negeri 1 Muara Bungo in writing news texts through the TTW strategy using photo events. The subject of this study was 30 students. The object of the research is the learning process of writing news texts through the TTW strategy using photo events. This classroom action research procedure is in the form of a cycle, cycle I consists of two meetings (3 hours of lessons), while cycle II consists of one meeting (2 hours of lessons). Each cycle consists of four main steps, namely planning, acting, observing, and reflecting. The instruments used were test and non-test instruments. Data analysis was performed using qualitative and quantitative techniques. From the results of the study it can be concluded that the ability to write news texts in Class XI OTKP students of SMK Negeri 1 Muara Bungo can be improved through the TTW strategy using event photos, the application of the TTW strategy using event photos can increase the development of 5W + 1H elements into interesting news texts. . Based on the results of the students' writing, the ability to write news texts increased from cycle I to cycle II. In the pre-cycle, 20% of students completed with a class average score of 59.17. In the first cycle, the average score increased to 6.43 and students' completeness was 63%. In the second cycle, the class average score increased to 81.9 and students' completeness was 93%.